The Effect Of Liquidity On Tax Avoidance With Capital Structure As An Intervening Variable In Islamic Commercial Banks In Indonesia In 2019-2023 - Arif Wansa; Shabrina Nurfadhilah Irwan; Safira Ainu Nadira Sofyan (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to determine the effect of liquidity on tax avoidance through capital structure as an intervening variable with the object of research being banking companies listed on the Indonesia Stock Exchange (IDX) gallery. The independent variable studied is liquidity by the Loan to Deposit Ratio (LDR). The independent variable studied is Tax Avoidance represented by the Effective Tax Rate (ETR), and the intervening variable studied is Capital Structure represented by the Debt Equity Ratio (DER). The population studied is all banking companies listed on the Indonesia Stock Exchange (IDX) gallery for the period 2019-2023. The type of research used is a quantitative method. The sampling technique uses a purposive sampling technique and takes 10 banking companies that meet the requirements for research. This study uses PLS (Partial Least Square) using the SmartPLS application version 4.0. The research results obtained show that 1) Liquidity has a significant effect on tax avoidance, 2) Liquidity has a significant effect on capital structure, 3) capital structure has a positive effect on tax avoidance, 4) liquidity is able to significantly influence tax avoidance through capital structure.